Human Mesenchymal Stromal Cells Transplantation May Enhance or Inhibit 4T1 Murine Breast Adenocarcinoma through Different Approaches - T. Jazedje; A. L. Ribeiro; M. Pellati; H. M. de Siqueira Bueno; G. Nagata; M. Trierveiler; E. G. Rodrigues; M. Zatz (Stem Cells International)
The use of Mesenchymal Stromal Cells (MSCs) aiming to treat cancer has shown very contradictory results. In an attempt to clarify the contradictory results reported in the literature and the possible role of human fallopian tube Mesenchymal Stromal Cells (htMSCs) against breast cancer, the aim of this study was to evaluate the clinical effect of htMSCs in murine mammary adenocarcinoma using two different approaches: (1) coinjections of htMSCs and 4T1 murine tumor cell lineage and (2) injections of htMSCs in mice at the initial stage of mammary adenocarcinoma development. Coinjected animals had a more severe course of the disease and a reduced survival, while tumor-bearing animals treated with 2 intraperitoneal injections of 106 htMSCs showed significantly reduced tumor growth and increased lifespan as compared with control animals. Coculture of htMSCs and 4T1 tumor cells revealed an increase in IL-8 and MCP-1 and decreased VEGF production. For the first time, we show that MSCs isolated from a single source and donor when injected in the same animal model and tumor can lead to opposite results depending on the experimental protocol. Also, our results demonstrated that htMSCs can have an inhibitory effect on the development of murine mammary adenocarcinoma.